2015
DOI: 10.3109/08880018.2015.1040933
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on the Causes of Delayed Diagnosis of Childhood Cancer in Ibadan, Nigeria

Abstract: Outcome in cancer may be improved by early diagnosis and prompt treatment. The objectives of this study were to determine the prediagnostic intervals (lag time) in childhood cancer and the factors that influence them at the University College Hospital (UCH), Ibadan. The study was prospective and observational and involved children diagnosed with cancer from July 2012 to June 2014 at UCH, Ibadan, Nigeria. A history of the illness was obtained and physical examination performed on each patient. Information obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…Consistent with results from previous studies, we found that awareness of cancers is high , although gaps exist in knowledge of linkages between modifiable and non‐modifiable factors and susceptibility to risk. Such knowledge is critical to enable individuals to take preventive action for enhancing their wellbeing.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with results from previous studies, we found that awareness of cancers is high , although gaps exist in knowledge of linkages between modifiable and non‐modifiable factors and susceptibility to risk. Such knowledge is critical to enable individuals to take preventive action for enhancing their wellbeing.…”
Section: Discussionsupporting
confidence: 90%
“…Lack of affordable local treatments options are amplified by long distances to treatment centers and transportation difficulties (38,39). Clinical care and transportation costs also play major roles in patient delay.…”
Section: Factors Associated With Delay and Abandonment Among Youth LImentioning
confidence: 99%
“…Studies highlight mismanagement of cancer cases at lower level facilities as a key weakness in health care systems which contributes to late stage of presentation and poor outcomes among children (40). Relatedly, parents who sought alternative sources of care had perceptions of unsatisfactory management by respective health facilities and a lack of confidence in health care systems (39). Alternative treatments were also sought due to the cost of modern medicine and the belief that alternative medicine had fewer side effects (41).…”
Section: Factors Associated With Delay and Abandonment Among Youth LImentioning
confidence: 99%
See 1 more Smart Citation
“…Annually, millions of cancer cases are found in the world. At the early stages, the diagnosis of cancerous cells are limited and complicated [12][13][14][15] ; One of the main problems in the cancer treatment is the lack of a suitable method for early diagnosis 16,17 . The big challenge associated with various cancers is the delayed diagnosis and the occurrence of metastasis 18,19 .…”
Section: Introductionmentioning
confidence: 99%